Management, recycling and reuse of waste composites - Goodship, Vannessa (Woodhead Publishing in materials., 2010)
This authoritative reference work provides a comprehensive review of the management, recycling and reuse of waste composites. These are issues which are of increasing importance due to the growing use of composites in many industries, increasingly strict legislation and concerns about disposal of composites by landfill or incineration. Part one discusses the management of waste composites and includes an introduction to composites recycling and a chapter on EU legislation for recycling waste composites. Part two reviews thermal technologies for recycling waste composites with chapters on pyrolysis, catalytic transformation, thermal treatments for energy recovery and fluidized bed pyrolysis. Part three covers mechanical methods of recycling waste composites. This section includes chapters on additives for recycled plastic composites, improving mechanical recycling and the quality and durability of mechanically recycled composites. Parts four discusses improving sustainable manufacture of composites, with chapters on environmentally-friendly filament winding of FRP composites, process monitoring and new developments in producing more functional and sustainable composites. Part five gives a review of case studies including end-of-life wind turbine blades, aerospace composites, marine composites, composites in construction and the recycling of concrete. With its distinguished editor and international team of contributors, Management, recycling and reuse of waste composites is a standard reference for anyone involved in the disposal or recycling of waste composites. Reviews the increasingly important issues of recycling and reuse as a result of the increased use of compositesDiscusses the management of waste composites and EU legislation with regards to recyclingExamines methods for recycling, including thermal technologies and mechanical methods.